PENGARUH LINGKUNGAN KERJA FISIK DAN LINGKUNGAN KERJA NON FISIK TERHADAP KEPUASAN KERJA KARYAWAN PT BP - Syahril sidiq, Muhammad; Ifah Masrifah; Sumardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT This study analyzes the partial and simultaneous effects of the physical and non-physical work environments on employee job satisfaction at PT BP. A quantitative method with a causal-associative approach was applied to 105 employees at a polymer masterbatch company in the Jababeka Industrial Area, Bekasi. A sample of 51 respondents was selected using the Slovin formula at a 10% error level and proportionate stratified random sampling. Data were collected through observation, documentation, and a five-point Likert questionnaire, then analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t tests, an F test, and the coefficient of determination in SPSS 26. The physical work environment had a positive and significant effect on job satisfaction (B = 0.602; t = 12.389; p < 0.001), as did the non-physical work environment (B = 0.586; t = 13.532; p < 0.001). Both variables simultaneously affected job satisfaction (F = 322.631; p < 0.001). The R-squared value of 0.931 indicates that the model explains 93.1% of the variation in job satisfaction. Improving physical conditions and social-psychological relations is therefore important for strengthening employee job satisfaction. Keywords: physical work environment, non-physical work environment, job satisfaction